Glass product and display device including the glass product

By introducing compression and tensile areas into glass products, using lithium aluminosilicate material and ion exchange process to accurately control stress distribution, the problem of insufficient strength in external impact of glass products is solved, and high strength and durability are achieved .

CN113526878BActive Publication Date: 2025-01-10SAMSUNG DISPLAY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202110318058.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-04-13
Filing Date
2021-03-25
Publication Date
2025-01-10
Estimated Expiration
2041-03-25

AI Technical Summary

Technical Problem

Existing glass products are insufficient in the face of external impact, making it difficult to effectively prevent rupture, and the stress distribution management is not accurate enough to meet customer needs.

Method used

By introducing compression and tensile areas into glass products, the stress distribution is accurately controlled, and materials such as lithium aluminum silicate are used to adjust the surface compression stress through an ion exchange process to form a symmetric compression stress distribution, thereby improving the strength of glass products.

Benefits of technology

It realizes the high strength of glass products, can effectively resist external impact, prevent cracks from spreading and rupture, and meets the requirements of lightness and durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113526878B_ABST
    Figure CN113526878B_ABST
Patent Text Reader

Abstract

The present application relates to a glass product and a display device including the glass product. The glass product includes: a first surface; a second surface opposite to the first surface; a first compression region extending from the first surface to a first compression depth; a second compression region extending from the second surface to a second compression depth; and a tensile region between the first compression depth and the second compression depth. The stress distribution of the first compression region includes a first segment between the first surface and a first turning point and a second segment between the first turning point and the first compression depth. The depth from the first surface to the first turning point ranges from 6.1 μm to 8.1 μm. The compressive stress at the first turning point ranges from 207 MPa to 254 MPa. The stress-depth ratio at the first turning point ranges from 28 MPa / μm to 35 MPa / μm.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to and the benefit of Korean Patent Application No. 10-2020-0044473, filed on Apr. 13, 2020, which is hereby incorporated by reference in its entirety. Technical Field

[0003] The present disclosure relates to a glass product and a display device including the glass product. Background Art

[0004] Glass products are widely used in electronic devices including display devices, building materials, etc. For example, glass products are applied to substrates of flat panel display devices such as liquid crystal displays (LCDs), organic light emitting displays (OLEDs), and electrophoretic displays (EPDs), or applied to cover windows of flat panel display devices for protecting the flat panel display devices.

[0005] As portable electronic devices such as smartphones and tablet PCs become popular, glass products applied to them are often exposed to external impacts. Therefore, it is beneficial to develop glass products that are thin and light for portability and can withstand external impacts. Attempts have been made to improve the strength of glass products by thermal strengthening or chemical strengthening, but more precise stress distribution management is required to meet customer needs. Summary of the invention

[0006] Aspects of the present disclosure are directed to glass articles having good strength through precise stress distribution.

[0007] Aspects of the present disclosure are also directed to a display device including a glass article having good strength through precise stress distribution.

[0008] However, aspects of the present disclosure are not limited to those set forth herein. The above and other aspects of the present disclosure will become more apparent to those of ordinary skill in the art to which the present disclosure pertains by referring to the detailed description of the present disclosure given below.

[0009] According to an embodiment, a glass product is provided, comprising: a first surface; a second surface opposite to the first surface; a first compression region extending from the first surface to a first compression depth; a second compression region extending from the second surface to a second compression depth; and a tensile region between the first compression depth and the second compression depth, wherein the stress distribution of the first compression region comprises a first segment between the first surface and a first turning point and a second segment between the first turning point and the first compression depth, wherein the depth from the first surface to the first turning point ranges from 6.1 μm to 8.1 μm, wherein the compressive stress at the first turning point ranges from 207 MPa to 254 MPa, and wherein the stress-depth ratio at the first turning point ranges from 28 MPa / μm to 35 MPa / μm.

[0010] The compression energy of the first compression zone can range from 12800 J / mm 2 Up to 15645J / mm 2 .

[0011] The first compression energy of the first segment may be less than the second compression energy of the second segment.

[0012] The magnitude of the second compression energy may be 2 to 5 times the magnitude of the first compression energy.

[0013] The first compression energy can range from 2866 J / mm 2 Up to 3504J / mm 2 , and the second compression energy can range from 9334J / mm 2 Up to 12141J / mm 2 .

[0014] The compressive stress at the first surface may range from 700 MPa to 950 MPa.

[0015] The compressive stress at the first turning point may be 0.218 to 0.363 times the compressive stress at the first surface.

[0016] The first compression depth may range from 125 μm to 135 μm.

[0017] A depth from the first surface to the first inflection point may be 0.045 to 0.065 times the first compression depth.

[0018] The first segment may have a first slope, the second segment may have a second slope, a tangent line of the stress distribution at the first turning point may have a third slope, and wherein an absolute value of the third slope may be smaller than an absolute value of the first slope and greater than an absolute value of the second slope.

[0019] An absolute value of the third slope may be in the range of 19 MPa / μm to 22 MPa / μm.

[0020] A y-axis intercept of a tangent line of the stress distribution at the first inflection point may be in a range of 350 MPa to 420 MPa.

[0021] The glass article may include lithium aluminosilicate.

[0022] The first compression depth may be a maximum penetration depth of sodium ions, and wherein the depth of the first turning point may be a maximum penetration depth of potassium ions.

[0023] The stress distribution in the second compression region may include a third segment between the second surface and the second turning point and a fourth segment between the second turning point and the second compression depth, wherein the depth from the second surface to the second turning point may range from 6.1 μm to 8.1 μm, wherein the compressive stress at the second turning point may range from 207 MPa to 254 MPa, and wherein the stress-depth ratio at the second turning point may range from 28 MPa / μm to 35 MPa / μm.

[0024] The stress distribution of the second compressive region may have a symmetrical relationship with the stress distribution of the first compressive region.

[0025] The maximum tensile stress in the tensile region may be in the range of 75 MPa to 85 MPa.

[0026] In a ball-on-the-ring (BOR) test of the glass article conducted on 10 or more samples using a 60 g ball, the median value of the defined drop height may be greater than or equal to 80 cm.

[0027] According to an embodiment, a glass product is provided, the glass product having a thickness of 0.45 mm to 0.8 mm, comprising: a first surface; a second surface opposite to the first surface; a first compression region extending from the first surface to a first compression depth; a second compression region extending from the second surface to a second compression depth; and a tensile region between the first compression depth and the second compression depth, wherein the compressive stress at the first surface ranges from 700 MPa to 950 MPa, wherein the first compression depth ranges from 125 μm to 135 μm, and wherein the stress distribution of the first compression region has an inflection point at a depth of 6.1 μm to 8.1 μm from the first surface and a compressive stress at the inflection point within a stress range of 207 MPa to 254 MPa.

[0028] In a ball-on-the-ring (BOR) test of the glass article conducted on 10 or more samples using a 60 g ball, the median value of the defined drop height may be greater than or equal to 80 cm.

[0029] The glass article may include lithium aluminosilicate.

[0030] According to an embodiment, a display device is provided, which includes: a display panel including a plurality of pixels; a cover window above the display panel; and an optically transparent adhesive layer between the display panel and the cover window, wherein the cover window includes: a first surface; a second surface opposite to the first surface; a first compression region extending from the first surface to a first compression depth; a second compression region extending from the second surface to a second compression depth; and a tensile region between the first compression depth and the second compression depth, wherein the stress distribution of the first compression region includes a first segment located between the first surface and a first turning point and a second segment located between the first turning point and the first compression depth, wherein the depth from the first surface to the first turning point ranges from 6.1 μm to 8.1 μm, wherein the compressive stress at the first turning point ranges from 207 MPa to 254 MPa, and wherein the stress-depth ratio at the first turning point ranges from 28 MPa / μm to 35 MPa / μm.

[0031] The cover window may include a glass article comprising lithium aluminosilicate and having a thickness of 0.45 mm to 0.8 mm, wherein the compression energy of the first compression region may range from 12800 J / mm 2 Up to 15645J / mm 2 , wherein the first compression energy of the first section can range from 2866 J / mm 2 Up to 3504J / mm 2 , wherein the second compression energy of the second section can range from 9334 J / mm 2 Up to 12141J / mm 2 , wherein the compressive stress at the first surface may range from 700 MPa to 950 MPa, and wherein the first compression depth may range from 125 μm to 135 μm.

[0032] According to the glass article and the display device according to the embodiment, the glass article and the display device may be implemented to have high strength by controlling (eg, precisely controlling) stress distribution so that they are not easily broken by external impact.

[0033] The aspects and features of the present disclosure are not limited to the aspects and features described above, and various other aspects and features are included in the present specification. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] The above and other aspects and features of the present disclosure will become more apparent by describing the embodiments of the present disclosure in more detail with reference to the accompanying drawings, in which:

[0035] Figure 1 is a perspective view of a glass article according to various embodiments;

[0036] Figure 2is a cross-sectional view showing an example in which a glass article according to an embodiment is applied to a cover window of a display device;

[0037] Figure 3 is a cross-sectional view of a glass product having a flat plate shape according to an embodiment;

[0038] Figure 4 is a flow chart showing operations of a method for manufacturing a glass product according to an embodiment;

[0039] Figure 5 It is schematically shown Figure 4 A diagram of the process from cutting to surface polishing after strengthening;

[0040] Figure 6 is a schematic diagram showing an ion exchange process according to an embodiment;

[0041] Figure 7 is a graph showing stress distribution of a glass article according to an embodiment;

[0042] Figure 8 yes Figure 7 An enlarged curve graph near the first compression region;

[0043] Fig. 9 It is schematically shown Figure 8 A graph of a linear curve approximated by the stress distribution of ;

[0044] Fig.10 is a schematic diagram showing stress distribution according to a plurality of stress-depth ratios of a first turning point;

[0045] Fig.11 is a schematic diagram showing stress distribution with various compression energies at the same stress-depth ratio at the first turning point;

[0046] Fig.12 is a graph showing stress at each position in the thickness direction of sample groups #1, #2, and #3; and

[0047] Fig.13 is a graph showing the results of the BOR test for sample groups #1, #2, and #3. DETAILED DESCRIPTION

[0048] By referring to the following detailed description and the accompanying drawings of the embodiments, the features of the present disclosure and the methods for realizing the same can be more easily understood. However, the present disclosure can be implemented in many different forms, and the present disclosure should not be interpreted as being limited to the embodiments set forth herein. On the contrary, these embodiments are provided so that the present disclosure will be thorough and complete, and the concept of the present disclosure is fully conveyed to those of ordinary skill in the art, and the present disclosure will be limited only by the appended claims and their equivalents. In the entire specification, the same reference numerals represent the same elements. As used herein, when the term "may" is used to describe the embodiments of the present disclosure, it means "one or more embodiments of the present disclosure". As used herein, the terms "substantially", "about", "approximately" and similar terms are used as approximate terms rather than as terms of degree, and are intended to leave a margin for the inherent deviation in the measured values ​​or calculated values ​​recognized by those of ordinary skill in the art. As used herein, unless the context clearly indicates otherwise, the singular forms "one (a)", "an" and "the" are also intended to include plural forms.

[0049] It will be understood that when an element or layer is referred to as being "on," "connected to," or "coupled to" another element or layer, it may be directly on, directly connected to, or directly coupled to the other element or layer, or there may be intervening elements or layers. Conversely, when an element or layer is referred to as being "directly on," "directly connected to," or "directly coupled to" another element or layer, there are no intervening elements or layers. As used herein, the term "and / or" includes any and all combinations of one or more of the relevant listed items.

[0050] In addition, any numerical range described herein is intended to include all sub-ranges of the same numerical precision contained within the described range. For example, the range of "1.0 to 10.0" is intended to include all sub-ranges between the described minimum value 1.0 and the described maximum value 10.0 (and including the minimum value 1.0 and the maximum value 10.0), that is, having a minimum value equal to or greater than 1.0 and a maximum value equal to or less than 10.0, such as, for example, 2.4 to 7.6. Any maximum numerical limit described herein is intended to include all smaller numerical limits contained therein, and any minimum numerical limit described in this specification is intended to include all larger numerical limits contained therein. Therefore, the applicant reserves the right to modify this specification, including the claims, to clearly describe any sub-ranges contained within the range explicitly described herein.

[0051] As used herein, the term "glass article" refers to an article made entirely or partially of glass.

[0052] Hereinafter, embodiments of the present disclosure will be described with reference to the accompanying drawings.

[0053] Figure 1 is a perspective view of a glass article according to various embodiments.

[0054] Glass is used as a cover window for protecting a display (e.g., a display panel or a display device), a substrate for a display panel, a substrate for a touch panel, an optical member such as a light guide plate, etc. in electronic devices including a display such as a tablet PC, a notebook PC, a smart phone, an e-book, a television set, and a PC monitor, as well as a refrigerator and a washing machine including a display screen. Glass can also be used as a cover glass for a dashboard of a vehicle, a cover glass for a solar cell, an interior material for a building material, a window for a building and a house, etc.

[0055] For some glass products, it is beneficial to have high strength. For example, when glass is used as a window, it is beneficial or desirable that the glass has a small thickness to meet the requirements of high transmittance and low weight, and it is also beneficial or desirable that the glass has strength so that it is not easily broken by external impact. Strengthened glass can be manufactured by, for example, chemical strengthening or thermal strengthening. Figure 1 Examples of tempered glass having various shapes are shown in FIG.

[0056] Reference Figure 1 In an embodiment, the glass article 100 may have a flat sheet shape or a flat plate shape. In another embodiment, the glass article 101, the glass article 102, and the glass article 103 may have a three-dimensional shape including a curved portion. For example, a surface (e.g., an upper surface or a lower surface) of each of the glass article 101, the glass article 102, and the glass article 103 may extend in three dimensions. For example, an edge of a flat portion (e.g., an upper surface or a lower surface) may be curved (e.g., glass article 101), or a flat portion may be integrally curved (e.g., glass article 102) or folded (e.g., glass article 103).

[0057] The planar shape of the glass articles 100 to 103 may be a rectangular shape, but is not limited thereto, and may have various suitable shapes, such as a rectangular shape with rounded corners, a square shape, a circular shape, and an elliptical shape. In the following embodiments, as an example of the glass articles 100 to 103, a flat plate having a rectangular planar shape is described, but the present disclosure is not limited thereto.

[0058] Figure 2 is a cross-sectional view illustrating an example in which a glass article according to an embodiment is applied to a cover window of a display device.

[0059] Reference Figure 2The display device 500 may include a display panel 200, a glass article 100, and an optically transparent adhesive layer 300, wherein the glass article 100 is disposed on the display panel 200 and serves as a cover window, and the optically transparent adhesive layer 300 is disposed between the display panel 200 and the glass article 100 to bond the display panel 200 and the glass article 100 to each other.

[0060] Examples of the display panel 200 may include not only self-luminous display panels such as an organic light-emitting display (OLED) panel, an inorganic electroluminescent (EL) display panel, a quantum dot (QED) display panel, a micro LED display panel, a nano LED display panel, a plasma display panel (PDP), a field emission display (FED) panel, and a cathode ray tube (CRT) display panel, but also light-receiving display panels such as a liquid crystal display (LCD) panel and an electrophoretic display (EPD) panel.

[0061] The display panel 200 includes a plurality of pixels PX, and can display an image by utilizing light emitted from each pixel PX. The display device 500 may further include a touch member. In an embodiment, the touch member may be embedded in the display panel 200. For example, since the touch member may be directly formed on the display member of the display panel 200, the display panel 200 itself may implement a touch function. In another embodiment, the touch member may be manufactured separately from the display panel 200, and then coupled (e.g., attached) to the top surface of the display panel 200 by an optically transparent adhesive layer.

[0062] The glass article 100 is disposed above the display panel 200 to protect the display panel 200. The size of the glass article 100 may be larger than that of the display panel 200 so that its side surface may protrude outward from the side surface of the display panel 200, but the present disclosure is not limited thereto. The display device 500 may further include a printed layer disposed on at least one surface of the glass article 100 at an edge portion of the glass article 100. The printed layer may prevent a frame area of ​​the display device 500 from being visible from the outside, or may reduce visibility of a frame area of ​​the display device 500 from the outside, and in some cases the printed layer may perform a decorative function.

[0063] The optically transparent adhesive layer 300 is disposed between the display panel 200 and the glass article 100. The optically transparent adhesive layer 300 is used to fix the glass article 100 on the display panel 200. The optically transparent adhesive layer 300 may include an optically clear adhesive (OCA), an optically clear resin (OCR), and the like.

[0064] Hereinafter, the strengthened glass article 100 will be described in more detail.

[0065] Figure 3 is a cross-sectional view of a glass product having a flat plate shape according to an embodiment.

[0066] Reference Figure 3 , the glass article 100 may include a first surface US, a second surface RS, and a side surface SS. In the glass article 100 having a flat plate shape, the first surface US and the second surface RS are main surfaces having a large area, and the side surface SS is an outer surface coupling (e.g., connecting) the first surface US and the second surface RS.

[0067] The first surface US and the second surface RS are opposite to each other in the thickness direction. For example, the first surface US may be the upper surface of the glass article 100, and the second surface RS may be the lower surface of the glass article 100. When the glass article 100 is used to transmit light in the same manner as a cover window of a display (for example, when the glass article 100 is used as a cover window), light may be mainly incident on one of the first surface US and the second surface RS, and may pass through the other.

[0068] The thickness t of the glass article 100 is defined as the distance between the first surface US and the second surface RS. The thickness t of the glass article 100 may range from, but is not limited to, 0.1 mm to 2 mm. As used herein, the term "mm" may refer to a distance equal to 10- 3 meters. In an embodiment, the thickness t of the glass article 100 may be about 0.8 mm or less. In another embodiment, the thickness t of the glass article 100 may be about 0.75 mm or less. In yet another embodiment, the thickness t of the glass article 100 may be about 0.7 mm or less. In yet another embodiment, the thickness t of the glass article 100 may be about 0.65 mm or less. In yet another embodiment, the thickness t of the glass article 100 may be about 0.6 mm or less. In yet another embodiment, the thickness t of the glass article 100 may be about 0.55 mm or less. In yet another embodiment, the thickness t of the glass article 100 may be about 0.5 mm or less. In yet another embodiment, the thickness t of the glass article 100 may be about 0.3 mm or less. In some embodiments, the thickness t of the glass article 100 may range from 0.45 mm to 0.8 mm or from 0.5 mm to 0.75 mm. The glass article 100 may have a uniform thickness t, but is not limited thereto, and may have a different thickness t for each region.

[0069] The glass article 100 may be strengthened to have a set or predetermined stress distribution therein. The strengthened glass article 100 more effectively prevents or reduces the generation of cracks, the extension of cracks, breakage, etc. caused by external impact than the glass article 100 before strengthening. The glass article 100 strengthened by the strengthening process may have different stresses for each region. For example, compression regions CSR1 and CSR2 to which compressive stress is applied may be provided near the surface of the glass article 100. For example, the compression region CSR1 may be at the first surface US (e.g., close to or adjacent to the first surface US), and the compression region CSR2 may be at the second surface RS (e.g., close to or adjacent to the second surface RS). A tensile region CTR to which tensile stress is applied may be provided inside the glass article 100. For example, the tensile region CTR may be between the compression region CSR1 and the compression region CSR2. The boundaries between the compression regions CSR1, CSR2 and the tensile region CTR (e.g., each of the boundaries between the compression region CSR1 and the tensile region CTR and the boundaries between the compression region CSR2 and the tensile region CTR) may have a stress value of zero. The stress value of the compressive stress in one compression region CSR1, CSR2 may vary according to the position (eg, depth from the surface). Also, the tension region CTR may have different stress values ​​according to the depth from the surface US, RS.

[0070] The positions of the compression regions CSR1, CSR2 in the glass article 100, the stress distribution in the compression regions CSR1, CSR2, the compression energy of the compression regions CSR1, CSR2, the tensile energy of the tensile region CTR, etc. have a great influence (e.g., effect) on the mechanical properties (such as surface strength) of the glass article 100. A more detailed description thereof will be given later.

[0071] Figure 4 is a flowchart illustrating operations of a method for manufacturing a glass product according to an embodiment. Figure 5 It is schematically shown Figure 4 A diagram showing the process from cutting to surface polishing after strengthening.

[0072] Reference Figure 4 and Figure 5 The method for manufacturing the strengthened glass product 100 may include a molding operation S1, a cutting operation S2, a side polishing operation S3, a surface polishing operation before strengthening S4, a strengthening operation S5, and a surface polishing operation after strengthening S6.

[0073] The molding operation S1 may include preparing a glass composition and molding the glass composition.

[0074] The glass composition may include (e.g., be) any suitable composition known or available in the art. In an embodiment, the glass composition may include (e.g., be) a lithium-alumina-silicon (LAS) glass ceramic containing lithium aluminum silicate. For example, the glass composition may include 50 to 80 mol% SiO 2 , 1 to 30 mol% Al 2 O 3 , 0 to 5 mol% B 2 O 3 , 0 to 8 mol% P 2 O 5 , 3 to 20 mol% Li 2 O, 0 to 20 mol% Na 2 O, 0 to 10 mol% K 2 O, 0 to 20 mol% MgO, 0 to 10 mol% CaO, 0 to 10 mol% SrO, 0 to 10 mol% BaO, 0 to 0.5 mol% SnO 2 , 0 to 10 mol% ZnO, 0 to 1 mol% TiO 2 , and 0 to 8 mol% ZrO 2 . As used herein, the term "mol%" may refer to the percentage of the number of moles of a component in a composition relative to the sum of all the number of moles of the composition. As used herein, the term "a content of 0 mol%" means that it substantially does not contain the corresponding component. As used herein, the term "(composition) substantially does not contain (a certain component)" means that the raw material, etc. does not intentionally contain the certain component, and includes, for example, the case where a trace amount (e.g., 0.1 mol% or less) of impurities is inevitably contained.

[0075] Regarding each component of the glass composition, in more detail, SiO 2 It constitutes the skeleton of the glass (e.g., the majority or largest component of the composition, measured in mol%, weight, etc.), can improve chemical durability, and can be used to reduce the occurrence of cracks when scratches (scratches) are caused on the glass surface. In order to fully achieve this effect, SiO may be contained in an amount of 50 mol% or more. 2 In order to exhibit (e.g., have) sufficient meltability, the SiO in the glass composition 2 The content may be as high as 80 mol%.

[0076] Al 2 O 3 Used to improve the fragility (or resistance to breakage) of glass. For example, when glass breaks, Al 2 O 3 Can be used to produce a smaller amount of fragments. For example, when glass breaks, it is less likely to break than when the glass does not contain Al2 O 3 Compared with the 2 O 3 The presence of Al can reduce the number of fragments into which the glass breaks. 2 O 3 It can be used as an active component to improve ion exchange performance (e.g., ion exchange rate or ion exchange amount) during chemical strengthening and to increase surface compressive stress after strengthening. 2 O 3 When the content of Al is 1 mol% or more, the above functions can be effectively performed. At the same time, in order to maintain the acid resistance and solubility of the glass, Al 2 O 3 The content of is preferably 30 mol% or less.

[0077] B 2 O 3 Enhance the chipping resistance of the glass and improve the fusibility of the glass. In some embodiments, B is not included 2 O 3 (0 mol%). In some embodiments, B may be included 2 O 3 , and when B 2 O 3 When contained in an amount of 0.5 mol% or more, the meltability of the glass can also be improved. 2 O 3 It may be beneficial or advantageous in inhibiting or reducing the occurrence of streaks during melting.

[0078] P 2 O 5 Improved ion exchange performance and crack resistance. In some embodiments, P 2 O 5 (0 mol%). In some embodiments, P may be included 2 O 5 , and when P 2 O 5 When contained in an amount of 0.5 mol% or more, the above functions can be significantly achieved. 2 O 5 It may be beneficial or advantageous in preventing or reducing the reduction in brittleness (or cracking resistance) and acid resistance, and the content (e.g., concentration) of 4 mol% or less of P 2 O 5 It may be more effective in preventing or reducing brittleness (or crack resistance) and reduction in acid resistance.

[0079] Li2 O is used to form (e.g., provide or improve) surface compressive stress through ion exchange. Lithium (Li) ions near the glass surface can be exchanged with sodium (Na) ions or the like through an ion exchange process. 2 O can also be used to improve the brittleness (or resistance to breakage) of glass. Li for efficient ion exchange 2 The content of O is 3 mol% or more, and in terms of acid resistance, Li 2 The content of O is preferably 20 mol% or less. For example, when the glass contains Li in an amount of 3 mol% or more and 20 mol% or less 2 O, then Li 2 O can improve ion exchange performance and can prevent or reduce the decrease in acid resistance.

[0080] Na 2 O is used to form surface compressive stress through ion exchange and improve the solubility of the glass. Na ions near the surface of the glass can be exchanged with potassium (K) ions or the like through an ion exchange process. In some embodiments, Na 2 O (ie, 0 mol%). In some embodiments, Na 2 O, and Na 2 The content of O is preferably 1 mol% or more to effectively achieve the above-mentioned effects. If only the Li and Na ion exchange process is performed without the K ion exchange process, in order to smoothly perform the Li and Na ion exchange, it may be preferable that Na 2 The content of O is 8 mol% or less. If a K ion exchange process is also performed, a larger amount of Na 2 However, also in this case, Na 2 The content of O is 20 mol% or less.

[0081] K 2 O improves ion exchange performance and is associated with fragility (or resistance to breakage). In some embodiments, K is not included. 2 In some embodiments, K may be included in an amount of 0.5 mol% or more. 2 O to improve ion exchange performance. In order to prevent excessive reduction in fragility (or crack resistance) or reduce the reduction in fragility (or crack resistance), K 2 The content of O may be 10 mol% or less.

[0082] MgO is used to increase surface compressive stress and improve the fragility (or crack resistance) of chemically strengthened glass. In some embodiments, MgO is not included. In some embodiments, MgO may be included in an amount of 3 mol% or more to effectively achieve the above effects. MgO in an amount of 20 mol% or less may be beneficial or advantageous in reducing the occurrence of devitrification during glass melting.

[0083] CaO is used to improve the solubility and brittleness (or crack resistance) of the glass. In some embodiments, CaO is not included. In some embodiments, in order to effectively achieve the above-mentioned effects, CaO is preferably included in an amount of 0.5 mol% or more. If the content of CaO is too high, the ion exchange performance may be reduced, and therefore, the content of CaO is preferably 10 mol% or less.

[0084] Similar to CaO, SrO is used to improve the solubility and brittleness (or crack resistance) of glass. In some embodiments, SrO is not included. In order to effectively achieve the above-mentioned effects, SrO is preferably included in an amount of 0.5 mol% or more. If the content of SrO is too high, the ion exchange performance may decrease, and therefore, the content of SrO is preferably 10 mol% or less.

[0085] BaO is used to improve the solubility and fragility (or crack resistance) of the glass. In some embodiments, BaO is not included. In order to effectively achieve the above effects, BaO is preferably included in an amount of 0.5 mol% or more. BaO in an amount of 10 mol% or less may be beneficial or advantageous in preventing excessive reduction in ion exchange performance or reducing reduction in ion exchange performance.

[0086] SnO 2 Used to improve the solubility of glass. SnO 2 Not only can it improve the solubility, but it can also be used as a clarifier (for example, a component that improves the transmittance of visible light). 2 If the content of SnO is too high, the transmittance may decrease, and therefore, 2 The content of SnO is preferably 0.5 mol% or less. In some embodiments, SnO is not included. 2 .

[0087] ZnO is used to improve the solubility of glass. In some embodiments, ZnO is not included. In some embodiments, ZnO may be included, and when ZnO is included in an amount of 0.25 mol% or more, the effect of improving solubility may be significantly exhibited. In order to prevent or reduce the reduction in weather resistance, the content of ZnO is preferably 10 mol% or less.

[0088] TiO 2Improve the brittleness (or resistance to breakage) of chemically strengthened glass. In some embodiments, TiO is not included. 2 In some embodiments, TiO 2 , and when TiO 2 When contained in an amount of 0.1 mol% or more, the effect of improving brittleness (or crack resistance) can be significantly exhibited. In order to prevent or reduce devitrification during melting, TiO 2 The content of is preferably 1 mol% or less.

[0089] ZrO 2 The surface compressive stress may be increased due to ion exchange and the fragility (or resistance to breakage) of the glass may be improved. In some embodiments, ZrO is not included. 2 In some embodiments, ZrO may be included. 2 , and when ZrO 2 When contained in an amount of 0.5 mol% or more, the above-mentioned effects can be effectively achieved. 2 May be beneficial or advantageous in inhibiting or reducing devitrification during melting.

[0090] In addition to the above components, the glass composition may also contain Y 2 O 3 ,La 2 O 3 , Nb 2 O 5 、 2 O 5 and Gd 2 O 3 In addition, as a clarifier, 0.5 mol% or less of Sb may be included. 2 O 3 、CeO 2 and / or As 2 O 3 The composition of the glass article 100 may be changed through a molding process, an ion exchange process, etc., which will be described later.

[0091] The glass composition can be molded into a flat glass shape by various suitable methods known or available in the art, for example, by a float process, a fusion drawing process, a slot drawing process, etc.

[0092] The glass molded into a flat plate shape can be cut by a cutting operation S2. The glass molded into a flat plate shape may have a size different from that of the final glass product 100. For example, glass molding may be performed to form a large-area substrate as a mother substrate 10a including a plurality of glass products (e.g., a plurality of glass products may be obtained from the mother substrate 10a). The mother substrate 10a may be cut into a plurality of glass units 10 to produce a plurality of glass products. For example, even if the final glass product 100 has a size (e.g., length) of about 6 inches, when the glass is molded into a size having a size several to several hundred times the size of the final glass product (e.g., 120 inches) and then cut, a plurality of glass products (e.g., 400 glass products) molded into a flat plate shape may be obtained at one time (e.g., from the mother substrate 10a). In this way, process efficiency may be improved compared to the case where a single glass product is molded separately. In addition, even when molding glass corresponding to the size of one glass product, if the final glass product 100 has a plane shape selected from a variety of suitable plane shapes, it may be made into a set, predetermined or desired shape by a cutting process.

[0093] The cutting of the glass (eg, the mother substrate 10 a ) may be performed using a cutting blade 20 , a cutting wheel, a laser, or the like.

[0094] The cutting operation S2 of the glass may be performed before the strengthening operation S5 of the glass. The mother substrate 10a may be strengthened once, and then the mother substrate 10a may be cut into the size of the final glass product 100. However, in this case, the cut surface (e.g., the side surface of the glass) may be in a non-strengthened state. Therefore, the strengthening operation S5 may be performed after the cutting is completed.

[0095] Between the cutting operation S2 and the strengthening operation S5 of the glass, a polishing operation before strengthening may be performed. The polishing operation before strengthening may include a side polishing operation S3 and a surface polishing operation S4 before strengthening. In an embodiment, after the side polishing operation S3 is first performed, the surface polishing operation S4 before strengthening may be performed, but the order may be reversed.

[0096] The side polishing operation S3 is an operation of polishing the side surface of the cut glass unit 10. In the side polishing operation S3, the side surface of the glass unit 10 is polished to have a smooth surface. In addition, through the side polishing operation S3, each side surface of the glass unit 10 may have a uniform surface (e.g., uniform roughness on the surface). For example, the cut glass unit 10 may include one or more cut surfaces. In some cut glass units 10, two of the four side surfaces may be cut surfaces. In some other cut glass units 10, three of the four side surfaces may be cut surfaces. In some other cut glass units 10, all of the four side surfaces may be cut surfaces. When the side surface is a cut surface, it may have a surface roughness different from the surface roughness of the uncut surface. In addition, even the cut surface may have a different surface roughness. Therefore, by polishing each side surface through the side polishing operation S3, each side surface may have a uniform surface roughness, etc. In addition, if there are small cracks on the side surface, they can be removed by the side polishing operation S3.

[0097] The side polishing operation S3 may be performed in parallel or simultaneously on a plurality of cut glass units 10. For example, in a state where a plurality of cut glass units 10 are stacked, the stacked glass units 10 may be polished simultaneously.

[0098] The side polishing operation S3 may be performed by a mechanical polishing method or by a chemical mechanical polishing method using the polishing apparatus 30. In an embodiment, two opposite side surfaces of the cut glass unit 10 may be polished in parallel or simultaneously, and then another two opposite side surfaces may be polished in parallel or simultaneously, but the present disclosure is not limited thereto.

[0099] The surface polishing operation S4 before strengthening may be performed so that each glass unit 10 has a uniform surface (e.g., uniform roughness on the surface). The surface polishing operation S4 before strengthening may be performed individually for each cut glass unit 10. However, when the chemical mechanical polishing apparatus 40 is sufficiently large compared to the glass unit 10, a plurality of glass units 10 may be horizontally arranged and then surface polished in parallel or simultaneously.

[0100] The surface polishing operation S4 before strengthening can be performed by chemical mechanical polishing. For example, the first surface and the second surface of the cut glass unit 10 are polished using a chemical mechanical polishing device 40 and a polishing slurry. In some embodiments, the first surface and the second surface of the cut glass unit 10 correspond to Figure 3 The first surface US and the second surface RS of the final glass article 100 shown in FIG. The first surface and the second surface may be polished in parallel or simultaneously. In some embodiments, one of the first surface and the second surface may be polished first, and then the other surface may be polished.

[0101] After the surface polishing operation S4 before strengthening, the strengthening operation S5 is performed. The strengthening operation S5 may include chemical strengthening and / or thermal strengthening. In the case where the glass unit 10 has a thin thickness of 2 mm or less, especially in the case of a thin thickness of about 0.75 mm or less, the chemical strengthening method may be suitably applied to precise stress distribution control. In the following embodiment, as an example, the case where the chemical strengthening method is applied to the strengthening operation S5 of the glass unit 10 will be described.

[0102] Chemical strengthening may be performed by an ion exchange process. An ion exchange process is a process of exchanging ions in the glass unit 10 with other ions. By performing the ion exchange process, ions at or near the surface of the glass unit 10 may be replaced or exchanged with larger ions having the same valence or oxidation state. For example, ions at or near the surface of the glass unit 10 may be replaced or exchanged with larger ions in a material (e.g., a solution) in contact with the surface of the glass unit 10. For example, when the glass unit 10 contains a monovalent alkali metal such as Li+, Na+, K+, and / or Rb+, the monovalent cations on the surface may be replaced with Na+, K+, Rb+, or Cs+ ions having a larger ionic radius. Referring to FIG. Figure 6 The ion exchange process is described in more detail.

[0103] Figure 6 is a schematic diagram illustrating an ion exchange process according to an embodiment. Figure 6 The figure shows the exchange of sodium ions and potassium ions inside the glass.

[0104] Reference Figure 6 , when a glass containing sodium ions is exposed to potassium ions by, for example, immersing the glass in a molten salt bath containing potassium nitrate, the sodium ions in the glass are discharged to the outside, and the potassium ions can replace the sodium ions in the glass. The exchanged potassium ions produce compressive stress because they have an ionic radius larger than that of sodium ions. The greater the amount of exchanged potassium ions, the greater the compressive stress. Because ion exchange is carried out through the surface of the glass, the amount (e.g., concentration) of potassium ions at the surface of the glass (e.g., on or near the surface of the glass) can be the largest (e.g., compared to other parts of the glass product). Although some of the exchanged potassium ions may diffuse into the glass to increase the depth of the compression region, such as the compression depth, the amount of exchanged potassium ions may generally decrease as it moves away from the surface. Therefore, the glass may have a stress distribution with a maximum compressive stress at the surface (e.g., on or near the surface) and a decrease toward the inside. However, the present disclosure is not limited to the above examples. The stress distribution may be modified according to the temperature, time, number (e.g., number of applications) of the ion exchange process, whether there is a heat treatment, etc.

[0105] Refer again Figure 4 and Figure 5 , the ion exchange process may be performed two or more times. For example, the ion exchange process may include a primary ion exchange process S51 and a secondary ion exchange process S52. The primary ion exchange process S51 and the secondary ion exchange process S52 may be performed in different baths 51 and 52. Each ion exchange process S51, S52 may be performed in parallel or simultaneously on a plurality of glass units 10. For example, by immersing a plurality of glass units 10 in one bath 51 or 52, an ion exchange process may be performed in parallel or simultaneously on a plurality of glass units 10. The ion exchange process will be described in more detail below.

[0106] After the strengthening operation S5, optionally, a surface polishing operation S6 after strengthening may also be performed. The surface polishing operation S6 after strengthening may remove fine cracks on the surface of the strengthened glass unit 10, and may control the compressive stress of the first surface and the second surface of the strengthened glass unit 10. For example, a float method, which is one of the suitable methods for producing a glass sheet, is performed by flowing a glass composition into a tin bath. In this case, the surface of the glass sheet in contact with the tin bath may have a different composition from the surface not in contact with the tin bath. Therefore, after the strengthening operation S5 of the glass unit 10, a deviation of compressive stress may occur between the surface in contact with the tin bath and the surface not in contact with the tin bath. However, by removing an appropriate thickness from the surface of the glass unit 10 through polishing, the deviation of compressive stress between the contact surface and the non-contact surface can be reduced. For example, the surface of the glass unit 10 in contact with the tin bath (for example, the thickness of the glass unit 10 at the surface) may be removed to reduce the deviation of compressive stress between the surface in contact with the tin bath and the surface not in contact with the tin bath.

[0107] The surface polishing operation S6 after strengthening may be performed by a chemical mechanical polishing method. For example, the first surface and the second surface of the strengthened glass unit 10 (which is the glass unit 10 to be processed) are polished using a chemical mechanical polishing device 60 and a polishing slurry. For example, the polishing thickness (for example, the depth to the first surface and / or the second surface of the glass unit 10 to be polished) may be set or adjusted within a range of 100 nm to 1000 nm, but the present disclosure is not limited thereto. As used herein, the term "nm" may refer to a thickness equal to 10-1000 nm. 9 The polishing thickness of the first surface and the second surface may be the same, but may be different.

[0108] After the surface polishing operation S6 after strengthening, a shaping process may be performed to shape the glass unit 10 into a set or predetermined shape. Figure 1 In the case of the three-dimensionally shaped glass products 101 to 103 shown in FIG, the three-dimensional processing process may be performed after the surface polishing operation S6 after strengthening is completed.

[0109] Hereinafter, stress distribution of the strengthened glass article 100 will be described in more detail.

[0110] Figure 7 is a graph showing stress distribution of the glass article 100 according to an embodiment. Figure 7 In the graph of , the X-axis represents the thickness t of the glass article 100. Figure 7 In the formula ( ), compressive stress has a positive value, while tensile stress has a negative value. Here, the magnitudes of compressive stress and tensile stress mean the magnitudes of absolute values ​​(eg, absolute stress values) regardless of their signs.

[0111] Reference Figure 7 , the glass article 100 includes a first compression region CSR1 extending (or extending) from the first surface US to a first compression depth DOC1 and a second compression region CSR2 extending (or extending) from the second surface RS to a second compression depth DOC2. The tension region CTR is disposed between the first compression depth DOC1 and the second compression depth DOC2 (e.g., between the first compression region CSR1 and the second compression region CSR2). The overall stress distribution in the glass article 100 may be symmetrical (e.g., reflection symmetric) between the first compression region CSR1 and the second compression region CSR2 extending from the first surface US and the second surface RS, respectively, relative to the center of the thickness t (e.g., relative to a plane extending through the center of the glass article 100). A compression region and a tension region may be disposed between opposite side surfaces of the glass article 100 in a similar manner.

[0112] The first compression region CSR1 and the second compression region CSR2 are resistant to external impacts to prevent or reduce the occurrence of cracks or breakages of the glass article 100. As the maximum compressive stresses CS1 and CS2 of the first compression region CSR1 and the second compression region CSR2 increase, the strength of the glass article 100 generally increases. Because external impacts are generally transmitted through the surface of the glass article 100, it is beneficial or advantageous in terms of durability to have the maximum compressive stresses CS1 and CS2 at the surface of the glass article 100. From this perspective, the compressive stresses of the first compression region CSR1 and the second compression region CSR2 tend to be maximum at the surface and generally decrease toward the inside.

[0113] The first compression depth DOC1 and the second compression depth DOC2 inhibit or prevent cracks or grooves formed in the first surface US and the second surface RS from extending to the tensile region CTR inside the glass article 100. As the first compression depth DOC1 and the second compression depth DOC2 increase, the extension of cracks, etc. can be more effectively prevented or prevented. The points corresponding to the first compression depth DOC1 and the second compression depth DOC2 correspond to the boundaries between the compression regions CSR1 and CSR2 and the tensile region CTR, and the stress value of the glass article 100 at this point is zero.

[0114] In the entire glass article 100, the tensile stress of the tensile region CTR may be balanced with the compressive stress of the compressive regions CSR1 and CSR2. For example, the total compressive stress (e.g., compressive energy) in the glass article 100 may be the same as the total tensile stress (e.g., tensile energy) in the glass article 100. The stress energy accumulated in a region having a constant width in the thickness t direction in the glass article 100 may be calculated as an integral value of the stress distribution. For example, the stress energy of the region may be an integral of the stress distribution across the corresponding width of the region. The stress distribution may be a function (e.g., f(x)) that provides a stress value of the glass article 100, which is a function of the depth (e.g., "x" in f(x)) from the surface of the glass article 100 in the thickness direction. When the stress distribution in the glass article 100 having a thickness t is expressed as a function f(x), the following relational expression may be established.

[0115] Mathematical expression 1

[0116]

[0117] The greater the magnitude of the tensile stress in the glass article 100, the more likely the fragments will be violently released (e.g., released with greater energy) when the glass article 100 breaks, and the more likely the glass article 100 will break from the inside (e.g., from the inside of the tensile region CTR). The maximum tensile stress that satisfies the fragility (or fracture resistance) requirements of the glass article 100 may satisfy, but is not limited to, the following relationship:

[0118] Mathematical Expression 2

[0119] CT1≤-38.7×ln(t)+48.2

[0120] In some embodiments, the maximum tensile stress CT1 may be 100 MPa or less, or 85 MPa or less. As used herein, the term "MPa" may refer to a value equal to 10 6Pascal's pressure. In some embodiments, the maximum tensile stress CT1 may be the maximum stress value of the tensile region CTR. A maximum tensile stress CT1 of 75 MPa or greater may be desirable to improve mechanical properties such as strength. In an embodiment, the maximum tensile stress CT1 may be greater than or equal to 75 MPa and less than or equal to 85 MPa, but the present disclosure is not limited thereto.

[0121] The maximum tensile stress CT1 of the glass article 100 may generally be located at a central portion of the thickness t of the glass article 100. For example, the maximum tensile stress CT1 of the glass article 100 may be located at a depth in a range of 0.4t to 0.6t, or at a depth in a range of 0.45t to 0.55t, or at a depth of about 0.5t.

[0122] Meanwhile, in order to increase the strength of the glass article 100, it is preferred that the compressive stress and the compression depths DOC1 and DOC2 may have large values. However, as the compression energy increases, the tensile energy also increases, and the maximum tensile stress CT1 may increase. In order to meet the brittleness (e.g., fragility) requirements (or crack resistance) while having high strength, it may be desirable to adjust the stress distribution so that the maximum compressive stresses CS1 and CS2 and the compression depths DOC1 and DOC2 have large values ​​and the compression energy becomes smaller. For example, the stress value of the glass article 100 may be highest at or near the surface of the glass article 100 and may decrease according to the depth away from the surface of the glass article 100. To this end, each of the first compression region CSR1 and the second compression region CSR2 may include a first turning point TP1 and a second turning point TP2, respectively, at which the slope of the stress distribution changes abruptly. The slope of the stress distribution may refer to the rate of change of the stress distribution relative to the depth from the surface of the glass article 100 in the thickness direction. The shape of the stress distribution (eg, the shape of the stress distribution in the compression region) can be precisely controlled by adjusting the process conditions of the primary ion exchange process and the secondary ion exchange process.

[0123] In the following, reference will be made to Figure 6 and Figure 7 A more detailed description of the stress distribution of the compression region is given. The following description will focus on the stress distribution of the first compression region CSR1. Because the first compression region CSR1 and the second compression region CSR2 have a symmetrical relationship in stress distribution (e.g., a reflection symmetrical relationship with respect to a plane extending through the center of the glass article 100), the repeated description of the stress distribution of the second compression region CSR2 may be simplified or not repeated. For example, the stress distribution of the glass article 100 extending from the first surface US to the first compression depth DOC1 may be substantially the same as the stress distribution of the glass article 100 extending from the second surface RS to the second compression depth DOC2.

[0124] Figure 8 yes Figure 7 An enlarged graph near the first compression region. Fig. 9 It is schematically shown Figure 8 Figure 2. A graph of a linear graph approximating the stress distribution.

[0125] Reference Figure 8 and Fig. 9 , the stress distribution in the first compression region CSR1 has a negative slope and generally decreases as it moves from the first surface US to the first compression depth DOC1. The stress distribution in the first compression region CSR1 includes at least one first turning point TP1 (or inflection point) at which the slope changes abruptly. For example, the stress distribution may have a relatively small radius of curvature at the first turning point TP1.

[0126] The first turning point TP1 is located between the first surface US and the first compression depth DOC1. The stress distribution may be divided into a first section SG1 and a second section SG2 based on the first turning point TP1. For example, the stress distribution may include a first section SG1 extending from the first surface US to the first turning point TP1 and a second section SG2 extending from the first turning point TP1 to the first compression depth DOC1.

[0127] The first segment SG1 and the second segment SG2 may be divided according to the type or kind of the permeated ions. For example, in the first compression region CSR1, potassium ions may permeate only into the depth portion of the first segment SG1 located relatively closer to the first surface US, and may not substantially permeate into the depth portion of the second segment SG2 located relatively inward. On the other hand, sodium ions having a smaller ion size than potassium ions may permeate not only into the depth portion of the first segment SG1 but also into the depth portion of the second segment SG2.

[0128] The stress of the first segment SG1 located relatively close to the first surface US in the first compression region CSR1 may be mainly determined by the density of potassium ions. As described above, a portion of the first segment SG1 may also include sodium ions, but the stress of the corresponding portion may mainly depend on the density of potassium ions having a larger ion size. In the depth portion of the first segment SG1, the greater the density of potassium ions, the higher the stress, and the stress distribution may be substantially similar to (e.g., may be substantially linearly related to) the density distribution of potassium ions. The first turning point TP1 may correspond to the maximum penetration depth of potassium ions.

[0129] The stress of the second segment SG2 located inwardly relative to the first compression region CSR1 may be mainly determined by the density of sodium ions. For example, in the depth portion of the second segment SG2, the greater the density of sodium ions, the higher the stress, and the stress distribution may be substantially similar to the density distribution of sodium ions. The first compression depth DOC1 may substantially correspond to the maximum penetration depth of sodium ions.

[0130] The first segment SG1 may be substantially approximated to a first straight line l1, which connects the coordinates of the first turning point TP1 (e.g., corresponding to the first turning point TP1) in the corresponding portion and the coordinates of the first surface US (e.g., corresponding to the first surface US). The first straight line l1 may be expressed as a first function in a coordinate plane having an X-axis indicating depth and a Y-axis indicating stress by the following mathematical expression 3:

[0131] Mathematical expression 3

[0132] y=m 1 x+a here, m 1 is the average slope of the first segment SG1, m 1 is the first slope of the first straight line l1, and a is the y-axis intercept, which represents the compressive stress at the first surface US.

[0133] The second segment SG2 may be substantially approximated by a second straight line l2 that connects the coordinates of the first turning point TP1 (e.g., corresponding to the first turning point TP1) in the corresponding portion and the coordinates of the first compression depth DOC1 (e.g., corresponding to the first compression depth DOC1) having a stress value of 0. The second straight line l2 may be expressed as a second function in a coordinate plane having an X-axis indicating depth and a Y-axis indicating stress by the following mathematical expression 4:

[0134] Mathematical Expression 4

[0135] y=m 2 x+b

[0136] Here, m 2 is the average slope of the second segment SG2, which is the second slope of the second straight line l2, b represents the y-intercept, and -b / m 2 is the x-axis intercept, which represents the first compression depth DOC1.

[0137] Some portions of the stretch region CTR adjacent to the first compression region CSR1 may have a stress distribution conforming to the second straight line 12. For example, the stress distribution of portions of the stretch region CTR adjacent to the first compression region CSR1 may be substantially approximated by the second straight line 12 when extrapolated into the stretch region CTR.

[0138] In the above function, the first slope m 1 and the second slope m2 Each of has a negative value, and the first slope m of the first straight line l1 1 The absolute value of the second straight line l2 is greater than the second slope m 2 The first segment SG1 may basically have a first slope m 1 , and the second segment SG2 may substantially have a second slope m 2 .

[0139] The slope (or gradient) of the stress distribution changes abruptly at the first turning point TP1. The first turning point TP1 is located at a point where the first straight line l1 and the second straight line l2 meet (e.g., cross or intersect) each other, but the second segment SG2 and the first segment SG1 in the actual stress distribution have an inflection point shape that is curved around the first turning point TP1. For example, the stress distribution of the first compression region CSR1 may have a smooth curve at and near the first turning point TP1. The stress distribution may have a third slope m at the first turning point TP1. 3 , and the third slope m 3 It can be calculated as the slope of the tangent line l3 of the stress distribution at the first turning point TP1. The third slope m 3 The tangent line l3 at the first turning point TP1 can be approximated as the slope of a straight line connecting a point of the first segment SG1 adjacent to the first turning point TP1 and a point of the second segment SG2 (e.g., a point of the second segment SG2 adjacent to the first turning point TP1). The tangent line l3 at the first turning point TP1 can be expressed as a third function in the following mathematical expression 5:

[0140] Mathematical Expression 5

[0141] y=m 3 x+c

[0142] The third slope m 3 has a negative value, and the third slope m 3 The absolute value of the first slope m 1 The absolute value of the second slope m 2 The absolute value of .

[0143] In an embodiment, the third slope m of the third function 3 The absolute value of may be in the range of 19 MPa / μm to 22 MPa / μm. In addition, the y-intercept c of the third function may be in the range of 350 MPa to 420 MPa. 3 can be about -19.678 MPa / μm, and the y-intercept c can be 387.35 MPa. When the third slope m of the third function 3 When the y-intercept c satisfies the above ranges, the magnitudes of the compression energy and the stress-depth ratio CDR of the first turning point TP1 can easily fall within preferred ranges to be described later.

[0144] The first segment SG1 and the second segment SG2 having different slopes may be produced by a plurality of ion exchange processes. The second segment SG2 may be produced by a primary ion exchange process, and the first segment SG1 may be produced by a secondary ion exchange process.

[0145] For example, the primary ion exchange process is a process of imparting compression depths DOC1 and DOC2 to the glass (e.g., imparting ions to the glass through the compression depths DOC1 and DOC2), and can generally be performed by exposing the glass to a single molten salt containing sodium ions or a mixed molten salt containing potassium ions and sodium ions. For example, for the primary ion exchange process, the glass is immersed in a first bath 51 containing a single molten salt containing sodium nitrate or a mixed molten salt mixed with potassium nitrate and sodium nitrate (see Figure 5 ). When a mixed molten salt is used, the contents (e.g., concentrations) of potassium nitrate and sodium nitrate in the first bath 51 may be similar. For example, the salt ratio (e.g., molar ratio, weight ratio, etc.) of potassium nitrate to sodium nitrate may be adjusted within a range of 40:60 to 60:40. In an embodiment, the salt ratio of potassium nitrate to sodium nitrate in the mixed molten salt of the primary ion exchange process may be 50:50, but is not limited thereto.

[0146] The primary ion exchange process may be performed within a temperature range of ±20°C of a temperature 50°C lower than the glass transition temperature (e.g., within a temperature range of 30°C to 70°C lower than the glass transition temperature). However, the present disclosure is not limited thereto. For example, when the glass transition temperature is about 580°C, the primary ion exchange process may be performed at a temperature of about 500°C or higher. The primary ion exchange process time may be within a range of 3 hours to 8 hours, but is not limited thereto.

[0147] Through the primary ion exchange process, lithium ions and / or sodium ions, which are small ions inside the glass, are exchanged with sodium ions and / or potassium ions, which are larger ions in the molten salt, thereby increasing the concentration of sodium ions and / or potassium ions in the glass. Since the molten salt is provided with lithium ions from the glass, the molten salt of the first bath 51 after the primary ion exchange process may also include lithium ions in addition to sodium ions and potassium ions.

[0148] After the primary ion exchange process and before the secondary ion exchange process, a stress relief process (or annealing process) may also be performed. The stress relief process may be performed at a temperature of about 500° C. or higher for 1 to 3 hours. The stress relief process may reduce the maximum compressive stress and allow sodium ions (and / or potassium ions) to diffuse into the glass to increase the compression depth. The stress relief process may be performed in air or liquid. The stress relief process may be omitted.

[0149] When the primary ion exchange process is completed (or, if a stress relief process is added, when the stress relief process is completed), a stress distribution corresponding to the second straight line l2 is generated. For example, sodium ions and / or potassium ions of the mixed molten salt are exchanged to penetrate into the glass and then diffuse in the depth direction (e.g., the thickness direction or toward the center of the glass product). The sodium ions generally diffuse to the first compression depth DOC1 to form a first compression region CSR1 having a compressive stress from the first surface US to the first compression depth DOC1. For example, the first compression depth DOC1 is determined by the primary ion exchange process and / or the stress relief process.

[0150] At the same time, the density of the diffused ions is substantially inversely proportional to the diffusion distance. Since the sodium ions and potassium ions enter the glass from the surface of the glass through ion exchange and diffuse in the depth direction, the concentration of the sodium ions and potassium ions tends to decrease linearly as the sodium ions and potassium ions move away from the first surface US of the glass article 100 (e.g., toward the center of the glass article 100). Therefore, the stress distribution has a maximum compressive stress CS1 at the first surface US of the glass article 100, and the stress distribution decreases in the depth direction in the same manner as the second straight line l2 (e.g., with the same slope as the second straight line l2).

[0151] In addition, the degree of diffusion of ions is inversely proportional to the size of the ions. For example, as the size of the ions decreases, more ions can diffuse and / or the ions can diffuse further. Therefore, when both sodium ions and potassium ions penetrate into the glass through the primary ion exchange process, the sodium ions, which have a relatively small size, may diffuse more easily and penetrate to a deeper level (e.g., compared to the potassium ions). The sodium ions may diffuse to the first compression depth DOC1, and the potassium ions may diffuse only to a depth less than or equal to the first turning point TP1.

[0152] As described above, the first compression depth DOC1 is closely related to the maximum diffusion depth of sodium ions, which are smaller ions that undergo ion exchange (for example, compared to potassium ions). The first compression depth DOC1 may be the same as the maximum diffusion depth of sodium ions, or even if slightly different, the first compression depth DOC1 may be located near the maximum diffusion depth. The first compression depth DOC1 may generally be proportional to the maximum diffusion depth of sodium ions. As described above, the primary ion exchange process and / or stress relief process is a process that forms a set or predetermined first compression depth DOC1 by sufficient diffusion, and is performed for a sufficiently long time to allow the ions to fully diffuse.

[0153] At the same time, as more ion diffusion is achieved, the maximum compressive stress CS1 can become smaller. For example, as ions diffuse away from the surface of the glass (for example, during the stress relief process), the maximum compressive stress CS1 can be reduced due to the decrease in the concentration of ions at the surface of the glass. The maximum compressive stress CS1 increases as the density of ions increases. Therefore, if the same number of ions enter the glass, the more they diffuse, the smaller the density and the smaller the compressive stress. For example, when a set amount of ions enters the glass at the surface of the glass, as the diffusion increases, the ion density and compressive stress at the surface of the glass decrease. As described above, because the primary ion exchange process has limitations on increasing the maximum compressive stress CS1 of the first surface US, a secondary ion exchange process is further performed after the primary ion exchange process to form a larger maximum compressive stress CS1.

[0154] The secondary ion exchange process is a process for increasing the maximum compressive stress CS1, and is generally performed by exposing the glass to a single molten salt containing potassium ions or a mixed molten salt containing potassium ions and sodium ions. For example, for the secondary ion exchange process, the glass that has undergone the primary ion exchange process is immersed in a second bath 52 containing a single molten salt containing sodium nitrate or a mixed molten salt mixed with potassium nitrate and sodium nitrate (see Figure 5 ) in the second bath 52. Nitrates are mixed. Even when a mixed molten salt is used, the salt ratio may be set or adjusted so that the main ions penetrating into the glass are potassium ions. For example, the content of potassium nitrate in the second bath 52 is greater than that in the primary ion exchange process, and further, the concentration of potassium nitrate may be greater than that of sodium nitrate. For example, the salt ratio (e.g., molar ratio, weight ratio, etc.) of potassium nitrate to sodium nitrate in the second bath 52 may be set or adjusted within a range of 80:20 to 98:2. In an embodiment, the salt ratio of potassium nitrate to sodium nitrate in the mixed molten salt of the secondary ion exchange process may be 92:8, but is not limited thereto.

[0155] Compared to the primary ion exchange process, the secondary ion exchange process may be performed at a lower temperature and for a shorter time. For example, the secondary ion exchange process may be performed for 1 to 3 hours, or for 1.3 to 2 hours, and may be performed at a temperature range of 380°C to 460°C.

[0156] Through the secondary ion exchange process, the compressive stress in the shallow depth portion of the glass surface such as the first surface US (for example, in the first segment SG1 or in the portion of the first segment SG1 closest to the first surface US) can be significantly increased. For example, when potassium ions penetrate into the glass, the compressive stress in the corresponding portion becomes greater due to the potassium ions having a larger size. The potassium ions that penetrate into the glass diffuse in the depth direction. Compared with the primary ion exchange process, potassium ions have a slower diffusion rate than sodium ions, and the duration of the secondary ion exchange process is shorter than the duration of the primary ion exchange process. In some embodiments, a higher percentage of ions entering the glass in the secondary ion exchange process are potassium ions compared to the primary ion exchange process. Therefore, the diffusion depth of the potassium ions diffused by the secondary ion exchange process may be much smaller than the first compression depth DOC1. As described above, the maximum diffusion depth of the potassium ions may be equal to or less than the first turning point TP1.

[0157] The stress distribution formed by (e.g., partially formed by) potassium ions that are additionally infiltrated by the secondary ion exchange process has substantially the same shape as the first straight line l1. The maximum compressive stress CS1 of the first surface US is increased by the secondary ion exchange process, while the penetration depth of potassium ions (or the first turning point TP1) is less than the first compression depth DOC1. Therefore, the first slope m of the first straight line l1 is 1 The absolute value of the second straight line l2 is greater than the second slope m 2 For example, the compressive stress distribution may have a steep slope near the surface of the glass article 100 (eg, in the first segment SG1) and become gentler (eg, smaller) toward the interior of the glass article 100 (eg, in the second segment SG2).

[0158] The stress distribution in the first compression region CSR1 as described above may have at least three main characteristic points.

[0159] The first characteristic point corresponds to the y-axis intercept of the second straight line l2 and is located at the first surface US (for example, on the first surface US). The second characteristic point corresponds to the x-axis intercept of the first straight line l1 and corresponds to the first compression depth DOC1. The third characteristic point is located at the first turning point TP1. The position of the characteristic point is a factor that basically determines the stress distribution. Since the stress distribution between the first characteristic point and the third characteristic point is approximately the first straight line l1 and the stress distribution between the second characteristic point and the third characteristic point is approximately the second straight line l2, when the first characteristic point, the second characteristic point and the third characteristic point are determined, the shape of the stress distribution can also be determined.

[0160] The first characteristic point is a point located at the first surface US (e.g., on the first surface US) and has an x-coordinate value of 0 and a y-coordinate value corresponding to the maximum compressive stress CS1. The maximum compressive stress CS1 represented by the first characteristic point is associated with the strength of the glass article 100. By increasing the maximum compressive stress CS1, the occurrence of cracks due to external impact can be prevented or reduced. The maximum compressive stress CS1 is mainly determined by the amount of potassium ions exchanged in the secondary ion exchange process, and may have a certain relationship with the degree of diffusion after the ion exchange.

[0161] The maximum compressive stress CS1 may be 300 MPa or greater. In various embodiments, the maximum compressive stress CS1 may be 350 MPa or greater, may be 400 MPa or greater, may be 450 MPa or greater, or may be 500 MPa or less. In addition, the maximum compressive stress CS1 may be 2000 MPa or less. In various embodiments, the maximum compressive stress CS1 may be 1800 MPa or less, may be 1500 MPa or less, or may be 1050 MPa or less. In some embodiments, the maximum compressive stress CS1 may be in the range of 700 MPa to 950 MPa.

[0162] The second characteristic point is a point where the stress value is 0, and has a y-coordinate value of 0 and an x-coordinate value corresponding to the first compression depth DOC1. The first compression depth DOC1 represented by the second characteristic point corresponds to the size (or width) of the first compression region CSR1 of the glass article 100. By increasing the first compression depth DOC1, it is beneficial or advantageous in preventing or stopping cracks from extending to the tension region CTR. From this perspective, the first compression depth DOC1 (i.e., the distance from the first surface US to the first compression depth DOC1) may be 50 μm or greater, may be 80 μm or greater, may be 100 μm or greater, or may be 125 μm or greater. As used herein, the term "μm" may refer to a distance equal to 10 -6 On the other hand, if the first compression depth DOC1 is too large, the compression energy and the tensile energy may be too large, which may result in failure to meet the fragility (or rupture resistance) requirements. From this point of view, the first compression depth DOC1 may be 250 μm or less, may be 200 μm or less, may be 180 μm or less, may be 150 μm or less, or may be 135 μm or less. In a preferred embodiment, the first compression depth DOC1 may range from 125 μm to 135 μm.

[0163] The first compression depth DOC1 may be mainly controlled by the temperature and time of the primary ion exchange process and / or the stress relief process. For example, the first compression depth DOC1 may be increased by increasing the time and / or temperature of the primary ion exchange process and / or the stress relief process.

[0164] Relative to the thickness t of the glass, the first compression depth DOC1 may be 0.1t (10% of the thickness t of the glass) or greater, may be 0.15t or greater, or may be 0.18t or greater. In addition, relative to the thickness t of the glass, the first compression depth DOC1 may be 0.25t or less, may be 0.23t or less, or may be 0.2t or less.

[0165] The third characteristic point is located at a set or predetermined depth and has a set or predetermined stress value. The first turning point TP1 represented by the third characteristic point and the first slope m of the first segment SG1 are 1 and the second slope m of the second segment SG2 2 The second slope m 2 It can be determined by the process conditions of the initial ion exchange process and the stress relief process, and the first slope m 1 It can be determined by the process conditions of the secondary ion exchange process.

[0166] The x-coordinate value (depth) of the first turning point TP1 has a value between 0 (0 μm) and the first compression depth DOC1, and the y-coordinate value (stress) of the first turning point TP1 has a value between 0 (0 MPa) and the maximum compression stress (e.g., maximum compression stress CS1). According to the example of the first compression depth DOC1 and the maximum compression stress CS1 as described above, the depth of the first turning point TP1 may be in a range greater than 0 μm and less than 8.1 μm, and the stress of the first turning point TP1 may be in a range greater than 0 MPa and less than 950 MPa. The position of the first turning point TP1 determines the basic shape of the stress distribution in the first compression region CSR1. In addition, the position of the first turning point TP1 determines the area of ​​the first compression region CSR1 (e.g., the magnitude of the compression energy).

[0167] If the depth DOL_TP1 of the first turning point TP1 from the first surface US is too large, production costs may increase, the magnitude of the compression energy may be too large, and / or mechanical properties such as strength may decrease. If the depth DOL_TP1 of the first turning point TP1 is too small, the portion that can effectively prevent or stop the expansion of cracks due to impact (e.g., strong impact) may be reduced. In view of the above, the depth DOL_TP1 of the first turning point TP1 may be in the range of 6.1 μm to 8.1 μm.

[0168] The ratio of the depth DOL_TP1 of the first turning point TP1 to the first compression depth DOC1 may be in the range of 0.045 to 0.065, or in the range of 0.049 to 0.06. Relative to the thickness t of the glass, the depth DOL_TP1 of the first turning point TP1 may be in the range of 0.005t to 0.015t, or in the range of 0.0087t to 0.0116t.

[0169] If the stress CS_TP1 of the first turning point TP1 is too large, the compression energy increases and / or the depth of the first turning point TP1 decreases, which makes it difficult to prevent or stop the expansion of the crack. If the stress CS_TP1 of the first turning point TP1 is too small, the strength (e.g., the strength of the glass) may become too small. From this point of view, the stress CS_TP1 of the first turning point TP1 may be in the range of 207 MPa to 254 MPa. The stress CS_TP1 of the first turning point TP1 may be in the range of 0.218 times to 0.363 times the maximum compressive stress CS1, or in the range of 0.267 times to 0.296 times the maximum compressive stress CS1.

[0170] In addition to the depth DOL_TP1 and the stress CS_TP1 of the first turning point TP1, the ratio of the stress CS_TP1 to the depth DOL_TP1 of the first turning point TP1 (hereinafter referred to as the stress-depth ratio CDR) is the main factor in determining the proportion of the compression energy of each segment SG1, SG2 in the stress distribution (for example, the value obtained by integrating each segment).

[0171] Fig.10 is a schematic diagram showing stress distribution according to a plurality of stress-depth ratios CDR of the first turning point TP1. Figure 8 , Fig. 9 and Fig.10 , as the stress-depth ratio CDR of the first turning point TP1 increases, the depth DOL_TP1 of the first turning point TP1 relatively decreases and / or the stress CS_TP1 of the first turning point TP1 relatively increases. In addition, the first compression energy (or surface compression energy) of the first segment SG1 relatively decreases, but the second compression energy (or internal compression energy) of the second segment SG2 relatively increases. On the other hand, when the stress-depth ratio CDR of the first turning point TP1 decreases, the opposite trend is shown.

[0172] According to the experiment, when the depth DOL_TP1 of the first turning point TP1 is in the range of 6.1 μm to 8.1 μm, the stress CS_TP1 of the first turning point TP1 is in the range of 207 MPa to 254 MPa. In addition, as the stress-depth ratio CDR of the first turning point TP1 increases, mechanical properties such as strength are improved. If the stress-depth ratio CDR of the first turning point TP1 is 28 MPa / μm or more, a significant strength improvement effect can be shown in the glass impact test (GIT). On the other hand, when the stress-depth ratio CDR of the first turning point TP1 is too large, the depth DOL_TP1 of the first turning point TP1 becomes smaller, and the portion corresponding to the first segment SG1 becomes too narrow. Since it is difficult to accurately form the stress distribution, there may be a lot of deviations between products. In addition, if the stress-depth ratio CDR of the first turning point TP1 is too large, the portion that can effectively prevent or stop the expansion of cracks caused by strong impact may be reduced, and the second compression energy may be further increased, thereby excessively increasing the total compression energy and tensile energy. From this point of view, the stress-depth ratio CDR of the first turning point TP1 can be preferably adjusted within a range of less than or equal to 35 MPa / μm. As described above, when the stress-depth ratio CDR of the first turning point TP1 is within a range of 28 MPa / μm to 35 MPa / μm, the second compression energy is greater than the first compression energy, and can be about 2 to 5 times or 3 to 4 times the first compression energy.

[0173] Fig.11 is a schematic diagram showing stress distribution with various compression energies at the same stress-depth ratio at the first turning point.

[0174] Reference Figures 8 to 11 , even when the maximum compressive stress CS1 as the first characteristic point and the first compression depth DOC1 as the second characteristic point are fixed and the stress-depth ratio CDR of the first turning point TP1 corresponding to the third characteristic point has a set value or a specific value, the compression energy and the tensile energy can be changed by the actual coordinates of the first turning point TP1. For example, even when the maximum compressive stress CS1 and the first compression depth DOC1 are set or fixed, the compression energy and the tensile energy can also have various suitable values. If both the stress CS_TP1 and the depth DOL_TP1 of the first turning point TP1 increase while maintaining the stress-depth ratio CDR, the stress distribution is located at a relatively high part (for example, the stress distribution generally increases), and therefore, the area under the curve increases to increase the compression energy and the tensile energy. A certain increase in compression energy is beneficial or advantageous in improving mechanical properties. For example, when the total compression energy obtained by adding the first compression energy and the second compression energy of the first compression region CSR1 is 12800 J / mm 2or greater, it has the effect of improving the mechanical properties in the glass impact test. On the other hand, excessive increase in tensile energy may result in failure to meet the requirements of fragility (or crack resistance) of the glass article 100. From this point of view, it is preferred that the total compression energy obtained by adding the first compression energy and the second compression energy of the first compression region CSR1 has a value of 15645 J / mm 2 For the second compression energy, the range of the second compression energy that can improve the mechanical properties and meet the fragility (or crack resistance) requirements can be from 9334 J / mm 2 Up to 12141J / mm 2 In addition, for the first compression energy, the first compression energy capable of improving the mechanical properties and satisfying the fragility (or crack resistance) requirements may range from 2866 J / mm 2 Up to 3504J / mm 2 The tensile energy is the sum of the compression energy of the first compression region CSR1 and the compression energy of the second compression region CSR2, and may be equal to twice the compression energy of each compression region. Therefore, considering the mechanical properties and fragility (or rupture resistance) requirements, the tensile energy may range from 25600 J / mm 2 Up to 31290J / mm 2 .

[0175] The compressive stress, the first compression depth DOC1, the tensile stress, the first turning point TP1, etc. as described above may be measured by a surface strain meter (FSM) and / or a scattered light polarizer (SLP).

[0176] For example, the first section SG1 associated with the maximum compressive stress CS1 and the first turning point TP1 can be measured by a surface stress meter (FSM), such as FSM-6000LE manufactured by Orihara Industrial Co., Ltd. (Japan). The surface stress meter can measure the density of potassium ions in the glass article 100. Therefore, the first section SG1 of the stress distribution can be estimated by measuring the density of potassium ions from the first surface US of the glass article 100 to the first turning point TP1, wherein the first turning point TP1 is the maximum penetration depth of potassium ions.

[0177] The first compression depth DOC1 can be measured by a scattered light polarizer (SLP) such as SLP-1000 manufactured by the above-mentioned company (Orihara Industrial Co., Ltd. (Japan)). SLP-1000 is used to examine the depth of deep stress in chemically strengthened glass having a lithium aluminum silicate composition. The scattered light polarizer (SLP) can measure the deep compression stress and internal stress of the glass product 100 using polarization. Stress distribution information can be obtained by combining the results of the compression stress near the surface measured by the surface stress meter (FSM) with the measurement results of the scattered light polarizer (SLP). In addition, the tensile stress is maximum at the center of the glass product 100, and has a stress value of zero when it reaches the first compression depth DOC1. Therefore, the point where the stress value measured by the scattered light polarizer (SLP) is zero can be estimated as the first compression depth DOC1, and the second segment SG2 can be estimated by connecting from the first compression depth DOC1 to the first turning point TP1.

[0178] It is apparent that the method of measuring stress distribution is not limited to the above-mentioned method, and may be measured by various other suitable devices and methods known or available in the art.

[0179] Hereinafter, the embodiments will be described in more detail through production examples and experimental examples.

[0180] Production Example 1: Production of tempered glass (1)

[0181] A plurality of plate-shaped glass substrates having a thickness of 0.80 mm and having a lithium aluminosilicate composition were prepared and divided into sample group #1, sample group #2, and sample group #3. Then, a chemical strengthening process was performed on each sample group.

[0182] Specifically, the glass substrate is subjected to a primary ion exchange process by immersing the glass substrate in a first molten salt bath in which potassium nitrate and sodium nitrate are mixed, and the glass substrate is subjected to a secondary ion exchange process by immersing the glass substrate in a second molten salt bath containing potassium nitrate. In order to compare the strength according to the stress distribution, the ion exchange process is performed on each sample group in different baths so that each sample group has a different stress distribution by the difference in temperature and time of the ion exchange process (e.g., according to the difference in temperature and time of the ion exchange process). The process conditions are adjusted so that the maximum compressive stress of each sample group corresponds to 800 MPa ± 20 MPa.

[0183] For the glass substrate that has completed the strengthening process, the stress at each position in the thickness direction is measured by FSM-6000LE and SLP-1000, and the results are shown in the following Table 1 and Fig.12 Shown in.

[0184] Table 1

[0185] Sample set #1 #2 #3 Maximum compressive stress (MPa) 797.4 801.5 783.7 Compressive stress at turning point (MPa) 141.7 147.9 230.8 Maximum tensile stress (MPa) 58.1 70.4 81.4 Turning point depth (μm) 9.3 8.6 7.4 First compression depth (μm) 142.8 156 130.6 Stress-depth ratio at the turning point (MPa / μm) 15.3 17.3 31.3 Compression energy (J / mm2) 10071.2 11838.1 14223.3

[0186] In addition, the tangent line equation at the turning point for each sample group was calculated as follows.

[0187] Table 2

[0188] Sample set Tangent line equation at the turning point #1 y=-10.902x+246.56 #2 y=-17.853x+310.13 #3 y=-19.678x+387.35

[0189] Experimental example: BOR (ball weight: 60g) test

[0190] A ball-on-ring (BOR) test was performed on sample group #1, sample group #2, and sample group #3, wherein the maximum compressive stress of sample group #1, sample group #2, and sample group #3 corresponded to 800 MPa±20 MPa. In order to evaluate according to the experimental example, 30 samples were prepared for each of sample group #1, sample group #2, and sample group #3. The BOR drop test was performed by placing and fixing the tempered glass sample on a ring and then dropping a 60 g ball onto the surface of the sample to check the height at which the sample was broken. The drop height of the ball was in the range of 30 cm to 100 cm. As used herein, the term "cm" may refer to a height equal to 10 -2 If no crack occurs when the ball is dropped, the ball drop is repeated by increasing the height by 5 cm. Finally, when cracks occur, the height immediately before the cracks occur (e.g., the maximum height at which no cracks occur) is determined as the limiting drop height (or critical drop height). Fig.13 Shown in.

[0191] Reference Fig.13 , the median value of the defined drop height in Sample Group #1 was measured to be 72.5 cm, and the median value of the defined drop height in Sample Group #2 was measured to be 75 cm. On the other hand, the median value of the defined drop height in Sample Group #3, which had a smaller maximum compressive stress than Sample Groups #1 and #2, was measured to be 87.5 cm. Therefore, Sample Group #3 was estimated to have a much higher surface strength than Sample Groups #1 and #2. For example, in a BOR test performed on 10 or more samples using a 60 g ball, Sample Group #3 exhibited a median defined drop height of 80 cm or more, indicating that Sample Group #3 had excellent surface strength.

[0192] Although the present disclosure has been shown and described with reference to the embodiments of the present disclosure, it will be understood by those skilled in the art that various appropriate changes may be made in form and details without departing from the spirit and scope of the present disclosure as defined by the appended claims and their equivalents. The embodiments should be considered in a descriptive sense only and not for the purpose of limitation.

Claims

1. Glass products, including: a first surface; a second surface, opposite to the first surface; a first compression region extending from the first surface to a first compression depth; a second compression region extending from the second surface to a second compression depth; as well as a stretching region between the first compression depth and the second compression depth, The stress distribution in the first compression region includes a first section between the first surface and the first turning point and a second section between the first turning point and the first compression depth. wherein the depth from the first surface to the first turning point ranges from 6.1 μm to 8.1 μm, The compressive stress at the first turning point ranges from 207 MPa to 254 MPa. wherein the stress-depth ratio at the first turning point ranges from 28 MPa / μm to 35 MPa / μm, and The compression energy of the first compression zone ranges from 12800 J / mm 2 Up to 15645J / mm 2 .

2. The glass product according to claim 1, wherein: A first compression energy of the first segment is less than a second compression energy of the second segment.

3. The glass product according to claim 2, wherein: The magnitude of the second compression energy is 2 to 5 times the magnitude of the first compression energy.

4. The glass product according to claim 3, wherein: The first compression energy ranges from 2866 J / mm 2 Up to 3504J / mm 2 , and the second compression energy ranges from 9334 J / mm 2 Up to 12141J / mm 2 .

5. The glass product according to claim 1, wherein: The compressive stress at the first surface ranges from 700 MPa to 950 MPa.

6. The glass product according to claim 5, wherein: The compressive stress at the first inflection point is 0.218 to 0.363 times the compressive stress at the first surface.

7. The glass product according to claim 1, wherein: The first compression depth ranges from 125 μm to 135 μm.

8. The glass product according to claim 7, wherein: The depth from the first surface to the first inflection point is 0.045 to 0.065 times the first compression depth.

9. The glass product according to claim 1, wherein: The first segment has a first slope, wherein the second segment has a second slope, wherein a tangent line of the stress distribution at the first turning point has a third slope, and The absolute value of the third slope is smaller than the absolute value of the first slope and larger than the absolute value of the second slope.

10. The glass product according to claim 9, wherein: The absolute value of the third slope is in a range of 19 MPa / μm to 22 MPa / μm.

11. The glass product according to claim 10, wherein: A y-axis intercept of the tangent line of the stress distribution at the first inflection point is in a range of 350 MPa to 420 MPa.

12. The glass product according to claim 1, wherein: The glass article comprises lithium aluminosilicate.

13. The glass product according to claim 1, in, The first compression depth is the maximum penetration depth of sodium ions, and Wherein, the depth of the first turning point is the maximum penetration depth of potassium ions.

14. The glass article according to claim 1, wherein: The stress distribution of the second compression area includes a third section between the second surface and the second turning point and a fourth section between the second turning point and the second compression depth, wherein the depth from the second surface to the second turning point ranges from 6.1 μm to 8.1 μm, wherein the compressive stress at the second turning point ranges from 207 MPa to 254 MPa, and Wherein, the stress-depth ratio at the second turning point ranges from 28 MPa / μm to 35 MPa / μm.

15. The glass product according to claim 14, wherein: The stress distribution of the second compression region has a symmetrical relationship with the stress distribution of the first compression region.

16. The glass article according to claim 1, wherein: The maximum tensile stress of the tensile region is in the range of 75 MPa to 85 MPa.

17. The glass article according to claim 1, wherein: In a ball-on-ring test of the glass article conducted on 10 or more samples using a 60 g ball, a median value of the drop height is defined to be greater than or equal to 80 cm.

18. Glass articles, with a thickness of 0.45 mm to 0.8 mm, comprising: a first surface; a second surface, opposite to the first surface; a first compression region extending from the first surface to a first compression depth; a second compression region extending from the second surface to a second compression depth; as well as a stretching region between the first compression depth and the second compression depth, wherein the compressive stress at the first surface ranges from 700 MPa to 950 MPa, Wherein, the first compression depth ranges from 125 μm to 135 μm, Wherein, the stress distribution of the first compression area has: an inflection point at a depth of 6.1 μm to 8.1 μm from the first surface; and a compressive stress at the inflection point in the stress range of 207 MPa to 254 MPa, and The compression energy of the first compression zone ranges from 12800 J / mm 2 Up to 15645J / mm 2 .

19. The glass article according to claim 18, wherein: In a ball-on-ring test of the glass article conducted on 10 or more samples using a 60 g ball, a median value of the drop height is defined to be greater than or equal to 80 cm.

20. The glass article according to claim 18, wherein: The glass article comprises lithium aluminosilicate.

21. A display device comprising: A display panel including a plurality of pixels; a cover window, above the display panel; as well as an optically transparent adhesive layer between the display panel and the cover window, Wherein, the cover window comprises: a first surface; a second surface, opposite to the first surface; a first compression region extending from the first surface to a first compression depth; a second compression region extending from the second surface to a second compression depth; and a stretching region between the first compression depth and the second compression depth, The stress distribution in the first compression region includes a first section between the first surface and the first turning point and a second section between the first turning point and the first compression depth. wherein the depth from the first surface to the first turning point ranges from 6.1 μm to 8.1 μm, wherein the compressive stress at the first turning point ranges from 207 MPa to 254 MPa, and The stress-depth ratio at the first turning point ranges from 28 MPa / μm to 35 MPa / μm. The compression energy of the first compression zone ranges from 12800 J / mm 2 Up to 15645J / mm 2 .

22. The display device according to claim 21, wherein: The cover window comprises a glass article comprising lithium aluminosilicate and having a thickness of 0.45 mm to 0.8 mm, The first compression energy of the first section ranges from 2866 J / mm 2 Up to 3504J / mm 2 , The second compression energy of the second section ranges from 9334 J / mm 2 Up to 12141J / mm 2 , wherein the compressive stress at the first surface ranges from 700 MPa to 950 MPa, and Wherein, the first compression depth ranges from 125 μm to 135 μm.

Citation Information

Patent Citations

  • Optical Device

    KR1020200044473A

  • Strengthened glass with ultra-deep depth of compression

    CN107074638A